Botanical Imperialism: The Stewardship of Plant Genetic Resources in the Third World - Broswimmer, Franz (Kasarinlan: Philippine Journal of Third World Studies; Vol 7 No 4 (1992), 2009)
Much of the literature on imperialism and underdevelopment focus narrowly on political economy. There is little attempt to examine the implicit "ecological" or "botanical" aspects of this global process. This essay aims to fill this gap by examining in more detail the botanical and ecological dimensions of this process.